One Intraoperative Dose of Tranexamic Acid for Patients Having Primary Hip or Knee Arthroplasty - Ralley, Fiona E. (Springer-Verlag, 2010)
BACKGROUND: Multiple studies suggest tranexamic acid reduces blood loss and red cell transfusions in patients undergoing THA or TKA. However, many of the dosing schedules in these studies are not ideally suited for routine application. QUESTIONS/PURPOSES: We asked whether one 20-mg per kg intraoperative dose of tranexamic acid in patients having primary THA or TKA would (1) decrease perioperative blood loss and red cell transfusion rates and (2) be a cost-effective protocol. PATIENTS AND METHODS: We retrospectively reviewed the records of 234 patients operated on from April 1 to June 30, 2007 (before our study protocol) and 259 patients from April 1 to June 30, 2008 with the single-dose protocol. We then compared change in hemoglobin, transfusion rates, hemoglobin at discharge, hospital length of stay, and complications between the two groups. No other routine patient care practices or blood conservation program strategies were altered during this time. RESULTS: We found a reduction in the decrease in hemoglobin in 2007 compared with 2008 for THA and TKA (46 to 39 g/L and 45 to 36 g/L, respectively), which led to a reduction in transfusion rates (13.5% to 3.6% and 13.1% to 2.0%, respectively) and higher hemoglobin levels at discharge. There were no recorded major adverse events associated with the introduction of this protocol. CONCLUSIONS: One 20-mg per kg intraoperative dose of tranexamic acid reduced the perioperative decrease in hemoglobin and red blood cell transfusion rates in patients having TKA and THA compared with those of a similar cohort of patients in whom the protocol was not used. This weight increment dosing facilitated pharmacy drug preparation, led to minimal dose variability and wastage, and resulted in a substantial estimated cost savings. LEVEL OF EVIDENCE: Level III, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.